More Than Frequency? Exploring Predictors of Word Difficulty for Second Language Learners. Issue 4 (16th May 2019) - Hashimoto, Brett J.; Egbert, Jesse
Abstract: Frequency is often the only variable considered when researchers or teachers develop vocabulary materials for second language (L2) learners. However, researchers have also found that many other variables affect vocabulary acquisition. In this study, we explored the relationship between L2 vocabulary acquisition and a variety of lexical characteristics using vocabulary recognition test data from L2 English learners. Conducting best subsets multiple regression analysis to explore all possible combinations of variables, we produced a best‐fitting model of vocabulary difficulty consisting of six variables ( R 2 = .37). The fact that many variables significantly contributed to the regression model and that a large amount of variance remained yet unexplained by the frequency variable considered in this study indicates that much more than frequency alone affects the likelihood that learners will learn certain L2 words. Abstract :